Analisis Faktor-Faktor yang Mempengaruhi Pemanfaatan Pengobatan Traditional - Anggreni, Dhonna; Diana, Sulis; Tonny, Harry Irfan (Journal of Telenursing (JOTING), 2023)
This research aims to analyze the factors that influence the use of traditional medicine at the Jember Acupuncture Center. The research method is an explanatory analytical research with a cross-sectional approach. The research results showed that most of the respondents' knowledge was in a suitable category, 36 people (60%), most of the family support was in an appropriate category, there were 32 people (58.3%), most of the sociocultural factors were supportive with the number of respondents being 28 people (45 .9%), and most of the use of traditional medicine is frequent with the number of respondents being 32 people (80.6%). In conclusion, there is a relationship between knowledge, family, and sociocultural support with using traditional medicine at the Jember Acupuncture Center. Keywords: Influencing Factors, Utilization of Traditional Medicine